Achieving green strategic objectives in business organizations within the green economy path and establishing the foundations of sustainable development: A theoretical and applied analysis – The case of the American Company Patagonia - Naima, Khaldi; Lahouel, Abdelkader (The International tax journal, 2026)
The transition to a green economy has become an urgent necessity following environmental degradation, manifested in the intensification of climate change and its devastating impacts. The green economy ensures environmental balance, and the study highlighted its role in promoting sustainable economic growth, thereby reducing environmental risks and mitigating global warming. It also provides new opportunities for wealth creation and sustainable employment, which represents a primary objective of the new strategic approaches to sustainable development that have become a key concern for states. The study emphasized the importance of adopting an environmental approach to achieve sustainable development by addressing and preventing environmental waste and making business activities environmentally friendly, whether through green products, the creation of green jobs, or other methods within the framework of promoting the green economy. Furthermore, the study concluded that Patagonia stands out as one of the world’s leading examples of a company implementing advanced green practices and embracing green economy principles. Through these approaches, Patagonia has been Enhancing its competitiveness and achieving added environmental and economic value.